Courage Of Alexia De Vere Reflected In Sidney Sheldon's The Tides Of Memory Novel (2013): A Feminist Approach - Anasyafitri, Ayuni, Dewi Candraningrum, Ph.D (2017)
This study has purposed to describe the courage of Alexia De Vere as the main character in the novel The Tides of Memory (2013) by Sidney Sheldon's using Feminism approach. The Tides of Memory (2013) novel analyzed with reference to two objects, such as: first, the analysis is based on a novel structural element, and the second is courage analysis based on Feminist approach. This study used a qualitative approach. This study uses two data sources: first, the novel The novel Tides of Memory (2013) Sidney Sheldon's works as the main data source. Second, the data source is taken from the book, author biographies, journals, Internet resources related to the research. Two types of data taken from libraries were analyzed using descriptive analysis. Based on the study, researchers concluded some conclusions. First, the structural elements of the novel gained through character and characterization, setting the place and time, plot, point of view, and the theme is arranged into a novel. Second, based on the approach Feminism is the participation of women, the women's role, women's rights, the position of women, and courage on the main character in the face of danger from his past in The Tides of Memory novel (2013). Keywords: Courage, structural elements of the novel, Feminist approach.